Diverse compounds from pleuromutilin lead to a thioredoxin inhibitor and inducer of ferroptosis - Llabani, Evijola; Hicklin, Robert W.; Lee, Hyang Yeon; Motika, Stephen E.; Crawford, Lisa A.; Weerapana, Eranthie; Hergenrother, Paul J. (Nature chemistry, 2019)
The chemical diversification of natural products provides a robust and general method for the creation of stereochemically rich and structurally diverse small molecules. The resulting compounds have physicochemical traits different from those in most screening collections, and as such are an excellent source for biological discovery. Herein, we subject the diterpene natural product pleuromutilin to reaction sequences focused on creating ring system diversity in few synthetic steps. This effort resulted in a collection of compounds with previously unreported ring systems, providing a novel set of structurally diverse and highly complex compounds suitable for screening in a variety of different settings. Biological evaluation identified the novel compound ferroptocide, a small molecule that rapidly and robustly induces ferroptotic death of cancer cells. Target identification efforts and CRISPR knockout studies reveal that ferroptocide is an inhibitor of thioredoxin, a key component of the antioxidant system in the cell. Ferroptocide positively modulates the immune system in a murine model of breast cancer and will be a useful tool to study the utility of pro-ferroptotic agents for treatment of cancer. A set of stereochemically complex and structurally diverse compounds were created from the diterpene natural product pleuromutilin using the complexity-to-diversity strategy. Phenotypic screening identified a compound that induces rapid ferroptotic death of cancer cells. Experiments to probe the mechanism revealed the compound to be an inhibitor of thioredoxin.